(untitled) (Mustansiria Dental Journal, 2018)
The aim study to evaluate whether Hydroxyapatite granules alone or in combination with autogenous bone marrow can facilitate bone formation. Materials and Methods: (8) dogs of both sexes were used as a model in this experimental study ,they were divided into two groups , the control group in which ( 4) dogs were operated on in this group received Hydroxyapatite granules alone in defect created in the body of mandible (1cm) in diameter and experimental group in which (4)dogs were operated on in this group received Hydroxyapatite granules mixed with autogenous bone marrow implanted in the defect also created in the body of mandible (1cm) in diameter .Alkaline phosphatase enzyme (ALP) used as parameter to evaluated the degree of osteogenesis ,so blood sampling from femur vein was aspirated at 1st ,2nd ,3rd and 4th weeks respectivelly for biochemical analysis .Results :Statistical analysis showed that there is significant elevation of serum (ALP) in experimental group at day 15 and 21 comparing to control group .Conclusion: Hydroxyapatite with autogenous bone marrow than it is used alone. has great effect on facilitating of osteogenesis.